If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10u = u + 36 Reorder the terms: 10u = 36 + u Solving 10u = 36 + u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-1u' to each side of the equation. 10u + -1u = 36 + u + -1u Combine like terms: 10u + -1u = 9u 9u = 36 + u + -1u Combine like terms: u + -1u = 0 9u = 36 + 0 9u = 36 Divide each side by '9'. u = 4 Simplifying u = 4
| 0.5w-13=20 | | 5v=v+12 | | 4(2w-1)=44 | | ln(x)+ln(2x)=2 | | 3h+3=21 | | 5x^2+x-9=0 | | -3x-9y=6 | | -3x^2-4x+10=0 | | x+2.5=.5(50+4x+5) | | x(x+3)-49=x(x-4) | | b(2a+3)=8a+12 | | 16a+69/3*56=300 | | (a+17)=54 | | 7+4x=39 | | 36=3(3*x) | | 3b*4b= | | 5x+4=7x+6 | | 3x^2+5y^2=60 | | 7(3k-4)=63 | | 2(2x+1)=30 | | 0.2f=1.2 | | x-8+2(7+x)=20-4x | | x-0.15x-47=0 | | 0.5a+2a=5 | | (x*23)-(4*x)=23 | | 4x-18=12-2x | | 10(x-6)=3(x+1) | | 6y=27 | | 12-8x=28-10x | | x^4+0x^3-2x^2+0x+1=0 | | (x+4)2=5 | | -6-10x=7x+19 |